IOTA Three-Step Strategy for Classifying Adnexal Masses: A Systematic Review and Meta-Analysis - Juan Luis Alcázar; Francisco Vargas; Guillem Boscá; Blanca Salazar; Juan Carlos Aguilar; Cynthia Catalan; Arleana Balazs; Daniela Burky; Magdalena Pertkiewicz; José Carlos Vilches; Rodrigo Orozco (Onco)
Background: Our goal was to assess the diagnostic performance of the IOTA 3-step strategy for discriminating benign from malignant adnexal masses. Methods: Systematic review and meta-analysis design. A systematic search across three databases (Medline [PubMed], SCOPUS, and Web of Science) was conducted to identify primary studies reporting on the use of the IOTA three-step strategy from January 2012 to July 2024. Prospective cohort studies utilizing the three-step strategy, with histologic diagnosis or conservative management confirming spontaneous resolution or persistence in cases of benign-appearing masses for at least one year of follow-up, were used as the reference standard. Studies unrelated to the topic, those not addressing the IOTA three-step strategy, studies focusing on other prediction models, letters to the editor, commentaries, narrative reviews, consensus documents, and studies lacking data for constructing a 2 × 2 table were excluded. Quantitative synthesis was done, calculating the pooled sensitivity, specificity, and positive and negative likelihood ratios. Qualitative synthesis was done using QUADAS-2. Results: A total of 448 citations were initially identified, with 7 studies meeting inclusion criteria, comprising 5722 patients. The mean prevalence of ovarian malignancy was 28%. The quality of the studies was considered good. IOTA 3-step strategy showed a pooled sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio of the three-step strategy for adnexal mass classification were 94% (95% CI = 91–95%), 94% (95% CI = 91–97%), 17.0 (95% CI = 10–28.8), and 0.07 (95% CI = 0.05–0.1), respectively. Heterogeneity for sensitivity was moderate, and for specificity it was high. Conclusions: We conclude that the three-step strategy has good diagnostic performance, reducing the need for expert examiner evaluation.